Implementasi Manajemen Peningkatan Mutu Madrasah - Yaqien, Nurul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Discussing about the implementation of madrasa quality increasement management is inseparable from the concept of management, roles and responsibility of management, the concept of quality, and how to implement madrasa quality increasement management itself. The effort of increasingquality of madrasa is basically conducted to face the competitive educational world, especially to face the issue of ASEAN community which starts from 2015. Furthermore, the big challenge for madrasa is how should madrasaprepare themself in increasing students’ competencies and all aspect related to instructional process. Therefore, the concept related to management, roles and responsibility of management, the concept of quality, and how to implement madrasa quality increasement management itself will bediscussed below.Keywords: Management, Quality, Madrasa.